Collection and Rearing of Container Mosquitoes and a 24-h Addition to the CDC Bottle Bioassay. Issue 6 (2nd November 2020) - Parker, Casey
Abstract: Container mosquitoes (Diptera: Culicidae) oviposit their eggs in both natural and artificial containers. Many container mosquito species also serve as important vectors of disease-causing pathogens including Aedes aegypti, Ae. albopictus, and Ae. triseriatus . Control of these species can be done through the use of adulticide sprays. The efficacy of these treatments is highly dependent on the insecticide susceptibility status of the local mosquito populations. This paper provides protocols on collecting and rearing container mosquitoes for use in the Centers for Disease Control and Prevention (CDC) bottle bioassay. A brief description of the CDC bottle bioassay is provided as well as a standardized protocol for the incorporation of a 24-h mortality to the CDC bottle bioassay. Results from this 24-h holding addition to the CDC bottle bioassay reveal that some forms of resistance may be missed without the incorporation of the additional mortality reading. These protocols provide a foundation for new laboratories to establish rearing protocols and begin conducting resistance monitoring.